A small heat shock protein, GmHSP17.9, from nodule confers symbiotic nitrogen fixation and seed yield in soybean. Issue 1 (17th September 2021) - Yang, Zhanwu; Du, Hui; Xing, Xinzhu; Li, Wenlong; Kong, Youbin; Li, Xihuan; Zhang, Caiying
Summary: Legume–rhizobia symbiosis enables biological nitrogen fixation to improve crop production for sustainable agriculture. Small heat shock proteins (sHSPs) are involved in multiple environmental stresses and plant development processes. However, the role of sHSPs in nodule development in soybean remains largely unknown. In the present study, we identified a nodule‐localized sHSP, called GmHSP17.9, in soybean, which was markedly up‐regulated during nodule development. GmHSP17.9 was specifically expressed in the infected regions of the nodules. GmHSP17.9 overexpression and RNAi in transgenic composite plants and loss of function in CRISPR‐Cas9 gene‐editing mutant plants in soybean resulted in remarkable alterations in nodule number, nodule fresh weight, nitrogenase activity, contents of poly β‐hydroxybutyrate bodies (PHBs), ureide and total nitrogen content, which caused significant changes in plant growth and seed yield. GmHSP17.9 was also found to act as a chaperone for its interacting partner, GmNOD100, a sucrose synthase in soybean nodules which was also preferentially expressed in the infected zone of nodules, similar to GmHSP17.9 . Functional analysis of GmNOD100 in composite transgenic plants revealed that GmNOD100 played an essential role in soybean nodulation. The hsp17.9 lines showed markedly more reduced sucrose synthase activity, lower contents of UDP‐glucose and acetyl coenzyme A (acetyl‐CoA), and decreased activity of succinic dehydrogenase (SDH) in the tricarboxylic acid (TCA) cycle in nodules due to the missing interaction with GmNOD100. Our findings reveal an important role and an unprecedented molecular mechanism of sHSPs in nodule development and nitrogen fixation in soybean.